2020
DOI: 10.21608/bvmj.2020.39010.1243
|View full text |Cite
|
Sign up to set email alerts
|

Some epidemiological studies on brucellosis in dairy farms in Gharbia governorate .Egypt.

Abstract: This study was conducted on dairy farms in Gharbia governorate, Egypt from January to December 2018. 240 dairy farms were included, and 3775 serum sample were collected for serological tests. 25 farms (10.42) were positive for brucellosis, 132 serum sample were positive by serological test classified according to the productive stage of animals as 121/3000 (4.033%), 8/600 (1.33%) and 2/175 (1.142%) in cows, heifers and bulls, respectively. The culturing and PCR confirmation results indicated that Brucella meli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
3
0
0
Order By: Relevance
“…Results of culturing of tissue samples from lymph nodes, spleen, liver, aborted foeti and milk were 13.7 %, 0.034 %, 0%, 25 % and 5.4% respectively table (6). These findings come in accordance with Aman et al et al (2020) 5 out of 200 (with an incidence rate of 2.5%) milk samples were positive for Brucella and grow on Brucella specific media On the other hand, a higher rate of isolation of Brucella organism reported by Khalafallah et al (2020) Results of culturing of tissue samples from lymph nodes, spleen and liver were 61.54%, 40.38% and 36.54% respectively H.I. Hosein et al (2017) 104 cows and 46 milk samples of sero-positive cows revealed isolation of 64 (61.5%) and 28 (60.9) brucella isolates respectively that were identified as Brucella melitensis biovar 3.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Results of culturing of tissue samples from lymph nodes, spleen, liver, aborted foeti and milk were 13.7 %, 0.034 %, 0%, 25 % and 5.4% respectively table (6). These findings come in accordance with Aman et al et al (2020) 5 out of 200 (with an incidence rate of 2.5%) milk samples were positive for Brucella and grow on Brucella specific media On the other hand, a higher rate of isolation of Brucella organism reported by Khalafallah et al (2020) Results of culturing of tissue samples from lymph nodes, spleen and liver were 61.54%, 40.38% and 36.54% respectively H.I. Hosein et al (2017) 104 cows and 46 milk samples of sero-positive cows revealed isolation of 64 (61.5%) and 28 (60.9) brucella isolates respectively that were identified as Brucella melitensis biovar 3.…”
Section: Discussionsupporting
confidence: 90%
“…melitensis DNA. The obtained results were agreed with that reported previously by Ilhan et al (2008) and El-Shymaa (2014)., Wareth et al (2015), who reported that PCR must be considered an alternative to the traditional culturing methods for Brucella diagnosis as screening and confirmatory diagnostic tool for saving cost and time, Also these results were similar to that obtained by Lobna M.A.et al, 2016, Khalafallah et al (2020.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation